PENGECEKAN PLAGIARISME PADA CODE DALAM BAHASA C++ - ., Liliana; Budhi, Gregorius Satia; Wibisono, Anthony; Tanojo, Ricky (Jurnal Informatika, 2012)
Informatics department of Petra Christian University has used to practice programming for students at programming studio, especially students who take algorithms and programming course. The system is currently implemented is to provide practice programming skill according to their ability. Assessment is done by calculating the points of all questions are done correctly. Problem which occurs at about the work in programming studio is plagiarism among students’ work. Unfortunately, plagiarism checking consumes a lot of time. In one semester, each student can do about 100 questions. If the total of students taking programming course, at least 100 people, we need many people to do this work. Departing from this problem, we design and develop an application to check for plagiarism between two different answer files from the same question. The degree of similarity is calculated using combined method of Jaccard similarity coefficient and cosine similarity coefficient. This system is able to check similarities in source code files are the work of students with moderate levels of complexity.